QUANTITATIVE ASSESSMENT OF ECO-ENVIRONMENT VULNERABILITY IN KARST REGION - Dongjie Guan; Weici Su (Lowland Technology International, 2014)
The Karst area is typical eco-environmental vulnerable area, where insufficient farmland and serious soil degeneration offer vulnerable ability to endure the natural disasters. Consequently, vulnerable eco-environment can’t coordinate with rapid social economic development, which leads to its feeble sustainable developmental ability. The Karst area of Chongqing in China as a study case , this paper sets up 13 influencing factors of eco-environment vulnerability to be assessment indexes, including earth surface of carbonate rock salt, area of mountainous region, area of slopping upland farming, degree of rock desertification (classified by gently, moderately, seriously), forest coverage, loss area of water and soil, soil erosion modulus, slip volume density, cultivation index, farmland area per capita, agriculture population density. Subsequently, the paper uses analytic hierarchy process (AHP) to endow indexes weight, and proposes an assessment model by using fuzzy mathematics method to analyze and assess the eco-environment vulnerability of Karst area. Finally, the assessment results are rankly divided. Results indicate: there are 3 potentially vulnerable counties, 10 gently vulnerable counties, 6 moderately vulnerable counties and 6 seriously vulnerable counties among the 25 Karst counties in Chongqing.